Myositis ossificans in the pediatric population: a systematic scoping review - Cherry, Ibrahim; Mutschler, Marion; Samara, Eleftheria; Merckaert, Sophie; Zambelli, Pierre-Yves; Tschopp, Benjamin (Frontiers in Pediatrics, 2023)
Introduction: Circumscribed or pseudomalignant myositis ossificans (MO) is a rare and benign condition characterized by heterotopic bone formation in soft tissues. The clinical presentation of MO, imaging investigations, histological findings, and treatment strategies are unclear, especially in the pediatric population. Materials and methods: A literature search was conducted in PubMed, Scopus, and Google Scholar electronic databases to identify original articles and reviews in English or French of traumatic and non-traumatic MO. Studies were selected by 2 independent reviewers following the PRISMA recommendation and descriptive data were extracted. We harvest in each case the sex, age at diagnosis, location, presence of initial trauma, pre-emptive diagnosis, modalities of imagery used, realized biopsy, treatment performed, and type of follow-up. Results: Sixty pediatric cases of MO were identified between 2002 and 2023. Twenty-three patients (39.3%) were diagnosed with idiopathic/pseudomalignant and 37 patients (60.7%) with circumscribed. The mean age at diagnosis was 9,5 years (range 0,2 -17 years), with a male-to-female ratio of 1:1. The initial pre-emptive diagnosis was neoplasia in 13 patients (21%). The biopsy was percutaneous in 7 patients (13%) and incisional in 6 patients (10%). Histological analysis was achieved in 35 cases (57%). Surgical excision was the first line treatment in 39% of patients, and non-surgical in the remaining patients. The follow-up strategy was clinical in 17 patients (28%) or based on imaging investigation in 42 patients (69%). Discussion: Although MO in children is described as a rare pathology, identifying the benignity of the condition is essential to avoid unnecessary invasive treatment and to avoid delaying the treatment of a potentially lifethreatening entity. It seems that there is no consensus established concerning the proper imaging for diagnosis. Clinicians should acknowledge that the absence of a triggering trauma tends to direct the investigation and the management toward a surgical attitude. Conservative management is key, however, surgical excision can be proposed on matured lesions on a case-by-case basis. The absence of recurrence is not excluded. Therefore, a close clinical follow-up is suggested for all cases. The true benefit of a radiological is questioned in a question known to be self-resolving.